Impact of Cyanide and Crude Protein Content in Host Plants on Yields and Residual Cyanide Content in Eri Silkworms (Samia ricini D.) - Duanpen Wongsorn; Arrisa Chueakhokkruad; Jurarat Pinwiset; Nittaya Pitiwittayakul; Benya Saenmahayak (Tropical Life Sciences Research, 2025)
This research investigated the impact of cyanide and crude protein content in host plants on feed consumption, survival rate, yield, and residual cyanide content in eri silkworms. The study utilised castor leaves from a native variety and cassava leaves from five varieties—Rayong 11, Rayong 72, Huai Bong 60, Kasetsart 50, and CMR43-08-89—which exhibited varying cyanide contents (53.66 to 365.22 mg/kg fresh weight) and crude protein contents (17.52% to 26.04% dry matter). Eri silkworms were reared under controlled laboratory conditions (25–32 ºC and 65–75 %R.H.) using a Completely Randomized Design (CRD). The survival rate of eri silkworms ranged from 80.00% to 94.66% and did not differ significantly (p > 0.05) among the different host plant treatments. However, castor leaves were the most consumed (20.8756 g/larva), resulting in higher cocoon weight (2.5990 g), pupa weight (2.2842 g), and fecundity (435.63 eggs/female moth) compared to cassava leaves (p < 0.05). Eri silkworms reared on Rayong 72 leaves had the lowest cocoon weight, pupa weight, shell weight, and fecundity. Cyanide content analysis in eri silkworms at the late fifth instar larvae stage showed no significant difference (5.71 to 6.33 mg/kg fresh weight, p > 0.05). However, the highest cyanide content was observed in pupae fed Rayong 72 leaves (14.92 mg/kg fresh weight), which significantly differed from other host plants (p < 0.05). In summary, cyanide and crude protein content in host plant leaves influenced the feed consumption, yield and cyanide residue in eri silkworms.